The impact of training and development on employee's productivity in Golden Tulip - Kumasi - Baah, Forson Kwame (2014)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the award of Master of Business Administration in Human Resource Management